Relationship maintenance strategies in web sites of companies listed on Bursa Malaysia - Dian Mariesta,; Emma Mohamad,; Arina Anis Azlan, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Effective relationship maintenance strategies between organisations and its public are able to help organisations to achieve its goals. In this study, researchers examined public relation strategies used by Malaysian companies to build their relationship with stakeholders through company websites. Based on Hon & Grunig’s relationship maintenance strategies, researchers analysed whether companies listed on Bursa Malaysia are utilising these strategies, and if so, how did they go about it? Quantitative content analysis was conducted to measure these strategies on 199 companies chosen using stratified sampling technique. The study found that access is the most commonly used strategy by companies listed on Bursa Malaysia, meanwhile a significant difference was observed among listed companies in terms of openness, networking and assurance strategies.